A New Normal in the Past: Learn from Historical Events in Bagelen After the Java War (1825-1830) - Ittihadiyah, Himayatul (Humanities Studies, Post-Graduate Program, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The article analyzes the historical mental situation in Bagelen after the Javanese War, a situation similar to the 'new normal' era. This term was popular towards the end of the COVID-19 pandemic when everyone was forced to adapt to a situation created by a power relation context as the 'new normal' era. In the context of the post-Java War era, the contestants, both winners and losers, were both forced to adapt to the colonial socio-cultural and political forces of the 'cultuurstelsel' era as the 'new normal'. This study explains how both sides adapted to the new normal, following their respective historical and devotional duties. The victor sought to explain his moral responsibility by building political legitimacy and new hopes in the form of imaginings of an age of prosperity in Bagelen, while the loser sought to atone for defeat by building a new civilization outside Bagelen. As the winner, R.A.A. Cokronegoro wrote an autobiographical account of the Java War which became known as Babad Kedung Kebo as the political legitimacy capital to build the city of Purworejo. At the same time, as the loser Prince Diponegoro also wrote an autobiographical account of the Java War which became known as Babad Diponegoro. As for his followers, consisting of the Kyai and students, they went into a diaspora, leaving the Bagelen area to build the city of Purworejo.